Trapped: The Limits of Care in California's Mental Health Courts - Cooper, Jessica (Social justice, 2017)
The article discusses the psychiatric care offered by mental health courts to prisoners in California, including the impact that U.S. neoliberalism has on options for prisoners. An overview of the prisoner Ramon Diaz's experience in the Santa Clara, California's mental health courts, including his desire to serve his prison time instead of receiving psychiatric care and Judge Stephen V. Manley's anger at this, is provided.